2011
DOI: 10.1111/j.1530-0277.2011.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Low Doses of Ethanol on Left and Right Ventricular Function in Young Healthy Subjects

Abstract: Low blood concentrations of ethanol acutely impair LV function and increase some indices of RV function in young healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
2
13
1
1
Order By: Relevance
“…There is limited data on the effects of alcohol on RV function, but it has been reported that low doses of alcohol in normal healthy individuals may lead to dilation of RV end-diastolic diameter and to an acute increase in some indices of RV function. 29 Conversely, studies on dogs reported that moderate or high doses of alcohol were associated with RV myocardial dysfunction in a dose-dependent manner. 30 …”
Section: Discussionmentioning
confidence: 99%
“…There is limited data on the effects of alcohol on RV function, but it has been reported that low doses of alcohol in normal healthy individuals may lead to dilation of RV end-diastolic diameter and to an acute increase in some indices of RV function. 29 Conversely, studies on dogs reported that moderate or high doses of alcohol were associated with RV myocardial dysfunction in a dose-dependent manner. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported inconsistent findings regarding the effect of alcohol intake on systolic cardiac function in asymptomatic people (Cameli et al., ; Kino et al., ; Lazarević et al., ; Reeves et al., ; Urbano‐Marquez et al., ; Zambrano et al., ). Two studies have found a slight increase in cardiac indices reflecting LV contractility (Cameli et al., ; Zambrano et al., ). Similarly, Urbano‐Marquez and colleagues () have reported that EF in alcoholics is lower than that in nonalcoholics.…”
Section: Discussionmentioning
confidence: 99%
“…Several echocardiographic studies have shown an increase in LV wall thickness and overall myocardial mass, or an increase in LV diastolic and systolic dimensions reflecting dilatation of LV of the heart in asymptomatic alcoholics (Kino et al., ; Lazarević et al., ; Mathews et al., ). In addition, a decrease in the ejection fraction (EF), suggesting a subclinical impairment of systolic function, was found in alcoholics (Cameli et al., ; Kupari et al., ; Urbano‐Marquez et al., ). A decrease in the peak early diastolic velocities of mitral inflow ( E peak) or the ratio of E peak over the peak late diastolic velocities of mitral inflow ( A peak), which indicates diastolic dysfunction, has also been found (Silberbauer et al., ; Zambrano et al., ).…”
mentioning
confidence: 99%
“…Cameli et al. (2011) have produced an interesting study in this issue which usefully contributes data on the effect of acute low‐dose alcohol (red wine) administration on blood pressure and ventricular function.…”
mentioning
confidence: 99%